A similarity criterion for spherical fuel elements free fall velocity in cylindrical channels with viscous liquid - Andrieieva, O.L.; Bulavin, L.A.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2021)
The introduction of nuclear high-temperature gas-cooled reactors (HTGR) with an active zone based on spherical fuel elements (SFE) poses the task of determining the velocity of their free fall in cylindrical channels with a viscous liquid. To solve it, the experimental data of other researchers are generalized, and for a certain range of Reynolds numbers the criterion of similarity for the velocity of free fall of spheres in cylindrical channels with water is found. The criterion is formulated on the basis of the Freud number. It is shown that from the dependence of the velocity of falling of the model sphere in a cylindrical vessel with water on the dimensionless diameter of the sphere, it is possible to determine the velocity of falling of the sphere in water, arbitrary. Впровадження атомних високотемпературних газоохолоджуваних реакторів (ВТГР) з активною канальною зоною на основі кульових твелів (КТ) ставить задачу з визначення швидкості їх вільного падіння в циліндричних каналах з в'язкою рідиною. Для її рішення узагальнені експериментальні дані інших дослідників, і для певного діапазону значень числа Рейнольдса знайдено критерій подібності для швидкості вільного падіння сфер у циліндричних каналах з водою. Зроблено висновок про те, що із залежності швидкості падіння модельної сфери в циліндричному каналі з водою від співвідношення діаметра сфери до діаметра каналу можна визначити залежність швидкості падіння у воді сфери довільного радіуса від співвідношення її діаметра до діаметра каналу. Внедрение атомных высокотемпературных газоохлаждаемых реакторов (ВТГР) с канальной активной зоной на основе шаровых твэлов (ШТ) ставит задачу по определению скорости их свободного падения в цилиндрических каналах с вязкой жидкостью. Для ее решения обобщены экспериментальные данные других исследователей, и для определенного диапазона изменения числа Рейнольдса найден критерий подобия для скорости свободного падения сфер в цилиндрических каналах с водой. Сделан вывод о том, что из зависимости скорости падения модельной сферы в цилиндрическом канале с водой от соотношения диаметра сферы с диаметром канала можно определить зависимость скорости падения в воде сферы произвольного радиуса от соотношения ее диаметра к диаметру канала.